Manajemen Kepemimpinan Pendidikan di Pesantren Berbasis Prinsip Progress of Change - Muhammad Madarik (Jurnal Tinta, 2025)
Islamic boarding schools (pesantren) are currently facing a critical phase of structural transition, moving away from traditional, single-figure leadership centered around the Kiai toward a more professional, collective management model. This study aims to formulate a strategic planning model for pesantren leadership transition based on the Islamic principle of "Progress of Change" (Taqaddum At-Taghyiir), derived from Surah An-Nahl verse 90. Using a qualitative-conceptual method with a managerial-theological approach, this study analyzes how strategic planning acts as a roadmap to bridge the current cultural conditions of pesantren with the ideal demands of modern institutional management. The results indicate that the integration of modern planning dimensions (macro, meso, micro) and multi-disciplinary approaches can successfully transform the pattern of pesantren authority without eroding its historical and spiritual values. This transition requires a participatory mechanism in compiling the Strategic Plan (Renstra) and Annual Work Plan (RKT), ensuring that the delegation of management responsibilities remains efficient, adaptive, and goal-oriented. Ultimately, this study contributes a new theoretical framework for Islamic educational management in navigating the tension between cultural preservation and professional disruption.